The Exile and Recalls of Arius - Barnes, Timothy D. (The journal of theological studies, 2009)
This article argues that after the Council of Nicaea in 325 Arius was exiled to Illyricum, then summoned to the imperial court in the winter of 327–8 by Constantine, who was however unable to effect his return to Alexandria. Some years later, Arius grew impatient at his continuing exclusion from Alexandria and wrote an injudicious letter to the emperor, who denounced him in a letter read out in Alexandria in the presence of the prefect Paterius. The article defends Eduard Schwartz's dating of this letter to 333 against the attempt of the editors of Athanasius Werke 3.1.3 (2007) to redate it to the 320s by setting out the full evidence for the chronology of the prefecture of Egypt between 324 and 334. It is further shown that Arius was recalled again in 335 and died in 336, not significantly earlier, as argued by the recent editors, and it is also suggested that Constantine issued his edict against Arius in 325 immediately after the Council of Nicaea, not in 333.